Uma análise de causalidade entre aspectos do desenvolvimento regional brasileiro : produto per capita, tamanho da população, qualificação da mão de obra e complexidade produtiva (2009-2019) - Ramos, Cesar Moser (2022)
This dissertation seeks to identify the causal relationship between the growth of gross domestic product, population variation, labor qualification and productive complexity in the development of Brazilian regions. The research used databases from the Ministry of Labor, the Brazilian Institute of Geography and Statistics and the National Institute of Educational Studies and Research. The data were organized and presented in the form of panels and cartographic maps, allowing us to observe which microregions had the greatest variation between 2009 and 2019. A multiple linear regression model was created to explain the variations observed in each of the variables. The results showed causal relationships between the variables and highlight the influence of regions with high GDP per capita on population growth and increase in the qualification of the workforce. Also, the skilled labor influences the productive complexity in the microregions. This study analyzed public data of a quantitative nature, without highlighting any specific influence of public policies and tax incentives.